Virtual Schooling and Student Learning: Evidence from the Florida Virtual School - Guido Schwerdt; Matthew M. Chingos (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Online education options have proliferated in recent years, with significant growth occurring at state-sponsored virtual schools. However, there is no prior credible evidence on the quality of virtual courses compared to in-person courses in U.S. secondary education. We compare the performance of students who took core courses in algebra and English at their traditional public high school to the performance of students who took the same courses through the Florida Virtual School, the largest state virtual school in the U.S. We find that FLVS students are positively selected in terms of prior achievement and demographics, but perform about the same or somewhat better on state tests once their pre-high-school characteristics are taken into account. We find little evidence of treatment effect heterogeneity across a variety of student subgroups, and no consistent evidence of negative impacts for any subgroups. Differences in spending between the sectors suggest the possibility of a productivity advantage for FLVS.
Keywords: I28; I21; J24; 330